Activation of sub-3 nm organic particles in the particle size magnifier using humid and dry conditions. (March 2022) - Rörup, B.; Scholz, W.; Dada, L.; Leiminger, M.; Baalbaki, R.; Hansel, A.; Kangasluoma, J.; Manninen, H.E.; Steiner, G.; Vanhanen, J.; Kulmala, M.; Lehtipalo, K.
Abstract: The accurate measurement of aerosol particles and clusters smaller than 3 nm in diameter is crucial for the understanding of new particle formation processes. The particle counters used for measuring these particles are typically calibrated with metal or salt particles under dry conditions, which does not always represent the field conditions where these instruments are later used. In this study, we calibrated the A11 nano Condensation Nucleus Counter (nCNC), consisting of the PSM (Particle Size Magnifier) and a laminar flow butanol based CPC (Condensational Particle Counter), with well-defined biogenic oxidation products from β-caryophyllene oxidation and compared it to a calibration with tungsten oxide under the same conditions. The organic particles were detected less efficiently than the inorganic ones. This resulted in a higher cut-off size for β-caryophyllene oxidation products than for tungsten oxide. At the same PSM settings, the cut-off size for tungsten oxide was 1.2 nm and for β-caryophyllene oxidation products 1.9 nm. However, repeating the calibration of the biogenic particles at 13% relative humidity at 31°C, increased their detection efficiency in the PSM, increasing the cut-off diameter to 1.6 nm. Additionally, we present a comparison of the ion concentrations measured with the PSM and the NAIS (Neutral Cluster and Air Ion Spectrometer) during new particle formation experiments in the CLOUD (Cosmics Leaving Outdoors Droplets) chamber. In these experiments, we produced particles from different organic precursors, such as α-pinene, β-caryophyllene and isoprene, as well as iodine. This way, we could determine the shift in cut-off diameter of the PSM for several different atmospherically relevant chemical compounds and compare it to the laboratory calibrations. We saw a diameter shift for the organic precursors of +0.3 nm in the PSM compared to the NAIS. These two approaches agreed well with each other and show that it is important to know the chemical composition of the measured particles to determine the exact size distribution using a supersaturation scanning method. Highlights: Accurate measurements of sub-3 nm particles are vital for the understanding of nucleation. Organic particles are not as well detected by CPCs than inorganic ones. Detection Efficiency of particle counters increases with increasing humidity.